2017
DOI: 10.1542/hpeds.2016-0071
|View full text |Cite
|
Sign up to set email alerts
|

Communication With Limited English-Proficient Families in the PICU

Abstract: OBJECTIVE Health care disparities have been described for children of limited English-proficient (LEP) families compared with children of English-proficient (EP) families. Poor communication with the medical team may contribute to these worse health outcomes. Previous studies exploring communication in the PICU have excluded LEP families. We aimed to understand communication experiences and preferences in the 3 primary communication settings in the PICU. We also explored LEP families’ views on interpreter use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…In our study setting, most of the parents were not efficient in understanding English whereas the physician and nurses did not have Arabic as their primary language. Studies have shown that language barrier can lead to suboptimal communication [32]. which can be minimized by increasing awareness and efficient use of interpreter.…”
Section: Discussionmentioning
confidence: 99%
“…In our study setting, most of the parents were not efficient in understanding English whereas the physician and nurses did not have Arabic as their primary language. Studies have shown that language barrier can lead to suboptimal communication [32]. which can be minimized by increasing awareness and efficient use of interpreter.…”
Section: Discussionmentioning
confidence: 99%
“…Among families with limited English proficiency, using an interpreter during rounds was associated with a decreased likelihood of correctly naming a diagnosis and less likelihood of understanding the medical plan after rounds compared with Englishspeaking families. 33,41 Englishspeaking families were more likely to report knowing discharge goals and the discharge day as compared with Spanish-speaking families. 38 Latino parents felt explanations in Spanish were essential for FCR 40 ; however, some felt disempowered to request interpreter services.…”
Section: Families With Limited English Proficiencymentioning
confidence: 96%
“…38 Latino parents felt explanations in Spanish were essential for FCR 40 ; however, some felt disempowered to request interpreter services. 36,41 With this research, it is suggested that families with limited English proficiency require additional support in FCR to promote participation and collaboration.…”
Section: Families With Limited English Proficiencymentioning
confidence: 99%
“…10 Over the course of the PICU stay, only 53% of families reported that the medical team used an interpreter most or all of the time, and 14% reported rarely or never receiving one. 2 Given that professional interpretation is necessary but not sufficient to achieve effective communication with LEP families and that effective communication is critical to providing high-quality, family-centered care, we have a long way to go in pursuit of equitable care delivery for LEP families. And although Ju et al were not able to explore precisely what factors led to the higher readmission rates among some groups of LEP families in their study, it seems clear that we are similarly falling short in achieving equitable outcomes.…”
mentioning
confidence: 99%